Insurance privatisation legal and financial issues - India International Law Foundation (New Delhi IIL Foundation, 2000)
Insurance privatisation consists some of the paper presented at the seminar on the legal and Financial issues facing the privatisation of the insurance sector in India the insurance sector in India.The insurance business market in India is porceived to be
Keywords: Insurance-India; Insurance law-India